Genome-Wide Identification and Expression Analysis of the CAMTA Gene Family in Roses (Rosa chinensis Jacq.) - Wanyi Su; Yuzheng Deng; Xuejuan Pan; Ailing Li; Yongjie Zhu; Jitao Zhang; Siting Lu; Weibiao Liao (Plants)
Calmodulin-binding transcription activator (CAMTA), as one of the transcription factors, is involved in performing important functions in modulating plant stress responses and development in a Ca2+/CaM-driven modus. However, genome-scale analysis of CAMTA has not been systemically investigated in roses. Rose (Rosa chinensis Jacq.) CAMTA gene family members were identified and bioinformatically analyzed to investigate their expression characteristics in plant hormonal responses. The results show that a total of five rose CAMTA genes were identified. Chromosomal localization shows that the RcCAMTA gene members were located on chromosomes 2, 4, and 7. Physicochemical property analysis shows that its CDS sequence length ranges from 500 to 1070 bp, the molecular weight ranges from 55,531.60 to 120,252.98 Da, and the isoelectric point is from 5.04 to 8.54. Phylogenetic analysis shows that rose CAMTA genes are classified into three subfamilies. Conservative motif analysis reveals the presence of motif 1, motif 3, motif 5, motif 7, and motif 10 in all the RcCAMTA genes. The cis-acting element prediction results show that the rose CAMTA gene family contains phytohormone-signaling response elements, abiotic stress responses, light responses, and other elements, most of which are hormone-signaling response elements. From the expression levels of RcCAMTA genes, the CAMTA family’s genes in roses have different spatial expression patterns in different tissues. The qRT-PCR analysis showed that all five rose CAMTA genes responded to salicylic acid (SA). RcCAMTA3 was significantly induced by abscisic acid (ABA), and RcCAMTA2 was significantly induced by 1H-indole-3-acetic acid (IAA) and methyl jasmonate (MeJA). Thus, we provide a basic reference for further studies about the functions of CAMTA proteins in plants.